The prince and the pauper - Twain, Mark; Schindler, S. D.; Twain, Mark, 1835-1910. (New York : Scholastic Inc., 1990)
When young Edward VI of England and a poor boy who resembles him exchange places, each learns something about the other's very different station in life.
Accelerated Reader
Keywords: Edward -- VI, -- King of England, -- 1537-1553 -- Juvenile fiction; Edward -- VI, -- King of England, -- 1537-1553 -- Fiction; Mistaken identity -- Fiction; Adventure and adventurers -- Fiction; England -- Fiction